Analysis of Shopping Malls in Lahore to Evaluate Design Provision for People with Special Needs - Ahsan, Rayyan; Awan, Usman; Iqbal, Mamuna (Annals of Human and Social Sciences, 2024)
This paper aims to examine need based facilities provisions in the shopping malls in Lahore like, washrooms, elevators, ATMs, parking and navigational aids, as important attributes. The research adopted quantitative and qualitative methods of data collection and analysis, consisting of research and analytical phases. The Research phase involved data collection, literature review, case studies, interviews, which are then used to inform the Analytical phase to draw conclusions, by comparative analysis of local and international shopping malls concerning the provision of facilities for handicapped users. The research findings suggest though there are facilities provided but improvements are needed in several areas, especially in terms of design considerations for physically challenged users. The research offers a framework and modular analysis of the selected study, providing a contextual approach for the development of architectural design. It also recommends design innovations in the selected mall to address the identified discrepancies and enhance the user experience for designers to consider.